The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00380261211052390
|View full text |Cite
|
Sign up to set email alerts
|

Enacting efficient care within a context of rationalisation

Abstract: Scholars have described how care cannot be completely commodified or withdrawn because it is a disposition anchored in the commitment to the needs of others. This article advances the literature on care ethics and inequality by examining how care workers resist and negotiate the rationalisation of care work. Building on ethnographic fieldwork on auxiliary nurses in Norwegian nursing homes, the study shows that despite care workers facing increasingly rationalised forms of control, they continue to act out of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…In contrast to previous studies (Doniol‐Shaw & Lada, 2011; Orupabo, 2022), the workers in this study do not seem to engage in any particular form of resistance. Even though resistance – in the form of, for example, speaking up – is considered the best way of achieving organisational change, it can be a confrontational and risky strategy not available to all categories of workers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies (Doniol‐Shaw & Lada, 2011; Orupabo, 2022), the workers in this study do not seem to engage in any particular form of resistance. Even though resistance – in the form of, for example, speaking up – is considered the best way of achieving organisational change, it can be a confrontational and risky strategy not available to all categories of workers.…”
Section: Discussioncontrasting
confidence: 99%
“…Unsurprisingly, recent transformations in the eldercare sector have affected the time available for care, increasing time pressure in work performance. Several studies have reported on time in social and eldercare work, for example in Ireland (McDonald et al, 2019), England (Hayes & Moore, 2017; Leverton et al, 2021; Rubery et al, 2015), France (Doniol‐Shaw & Lada, 2011), Canada (Sims‐Gould & Martin‐Matthews, 2010), Finland (Hirvonen & Husso, 2012; Leinonen, 2020), Denmark (Tufte, 2013; Tufte & Dahl, 2016), Norway (Bergschöld, 2018; Orupabo, 2022) and Sweden (Andersson, 2007; Strandell & Stranz, 2022). In addition to focusing on temporal dilemmas, scarcity of time, and staff experiences of time pressure, some of these studies have also been concerned with the psychosocial consequences of time constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies, representing different research disciplines such as social policy (e.g., Anttonen & Karsio, 2017;Burau et al, 2017;Szebehely & Meagher, 2018) and the sociology of work (Kamp & Hvid, 2012;Orupabo, 2022) have assessed and explained changes in the eldercare sector as consequences of NPM reforms.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies, representing different research disciplines such as social policy (e.g., Anttonen & Karsio, 2017; Burau et al, 2017; Szebehely & Meagher, 2018) and the sociology of work (Kamp & Hvid, 2012; Orupabo, 2022) have assessed and explained changes in the eldercare sector as consequences of NPM reforms. Researchers have typically focused on topics such as contract and control practices related to competitive tendering (Almquist, 2004; Szebehely & Meagher, 2013), free choice models (Rostgaard, 2011), performance and quality management (Hoppania et al, 2021; Vabø, 2012).…”
Section: Introductionmentioning
confidence: 99%